Progress and Innovative Combination Therapies in Trop-2-Targeted ADCs - Yizhi Jiang; Haiting Zhou; Junxia Liu; Wentao Ha; Xiaohui Xia; Jiahao Li; Tengfei Chao; Huihua Xiong (MDPI AG, 2024)
Precise targeting has become the main direction of anti-cancer drug development. Trophoblast cell surface antigen 2 (Trop-2) is highly expressed in different solid tumors but rarely in normal tissues, rendering it an attractive target. Trop-2-targeted antibody-drug conjugates (ADCs) have displayed promising efficacy in treating diverse solid tumors, especially breast cancer and urothelial carcinoma. However, their clinical application is still limited by insufficient efficacy, excessive toxicity, and the lack of biological markers related to effectiveness. This review summarizes the clinical trials and combination therapy strategies for Trop-2-targeted ADCs, discusses the current challenges, and provides new insights for future advancements.